DEVELOPMENT OF COMMUNITIES OF TRADERS AND PRIVATE HOUSEHOLDS IN REALIZING INDEPENDENT WELFARE THROUGH THE MOVEMENT OF LOVE TO SAVING SHARE (GERMAS) IN GAMPONG BLANG PULO AS A EXAMPLE OF GAMPONG INVESTMENT - Khaddafi, Muammar; Nur Ilham, Rico; Fuadi, Fuadi; Marzuki, Marzuki; Juanda, Reza (RADJA PUBLIKA, 2021)
In the industrial era 4.0 technology has emerged and people's thoughts are increasingly democratic. Nowadays, we see a lot of phenomena in coffee shops where young people with their laptops can buy company shares through investment and get dividends. This investment activity will encourage a country's economy, absorb labor, increase output resulting in foreign exchange savings or even increase foreign exchange. Investment aims to get a fixed income in each period, meet future needs and so on. Thus, the increase in the value of this investment is expected to help economic growth for the welfare of the community. (www.idx.co.id) The condition of the community in Blang Pulo Village is in a position that is still in the lower middle-class community where most people earn from farming and trading. Almost the average community does not have savings prepared for the future. Others are in a weak economic position where their income is only enough for their daily meals. With the investment village, it is hoped that the trading community in Gampong Blang Pulo will be willing to follow directions to save shares every month on a regular basis to get the maximum profit possible. (https://kampungkb.bkkbn.go.id) An investment village is an activity to introduce investment to the community and invite people to save shares. As well as providing guidance on how to invest properly and correctly that can generate future returns without any element of usury. With the investment village program, it is expected to be able to develop the potential that has been pioneered by the community to be more developed. The investment village will be held in Gampong Blang Pulo and will be assisted by local village officials in its implementation. The Investment Village Extension activity began with recording and visiting people's homes and then making friendly gatherings to increase friendship. After that, conducting counseling to invite people to save shares regularly every month and provide guidance on the capital market and conduct socialization in Gampong Blang Pulo to make the investment village program a success.